Optimizing Transparency in Procurement of Goods and Services in Luwu Regency through the LPSE System and Strengthening Regulatory Integrity - Rayhan, Muh.; Aiman, Nurafni (Moccasin Journal De Public Perspective, 2025)
Transparency in the procurement of goods and services is a key instrument for achieving accountable, efficient, and corruption-free governance. In Luwu Regency, the implementation of transparency through the Electronic Procurement Service (LPSE) system and Presidential Regulation No. 16 of 2018 and its amendments still faces challenges related to information disclosure, limited certified procurement personnel, local supplier participation, and public oversight mechanisms. This study aims to analyze the level of procurement transparency in Luwu Regency using Gregorius Porumbescu et al.’s (2022) Government Transparency framework, emphasizing organizational actors, information technology, managerial intervention, and stakeholder engagement. The research employs a qualitative descriptive case study approach using document review, interviews with ULP and PPK officials, suppliers, and field observations. The findings show that procedural transparency is achieved through LPSE use and public procurement plans, but substantive transparency remains low in bid evaluation disclosure, contract access, and project reporting. Technological transparency exists, yet organizational and managerial responsiveness is limited. To address this, the study adds a Regulatory Integrity dimension reflecting compliance, internal supervision, and sanctions enforcement. Transparency in Luwu Regency is still administrative rather than participatory, requiring stronger human resources, LPSE optimization, and participatory monitoring systems.